CMOS design and implementation of sigma-delta analog-to-digital data converter suitable for MEMS devices - Nordin, Anis Nurashikin; Zaghloul, Mona E. (2002)
MicroElectroMechanical systems (MEMS) are rapidly gaining popularity over a wide range of applications today. An example of full integration in MEMS is the smart sensor where both the sensors and the electrical signal processing circuitry are placed on the same chip. The idea is to place the sensor as close as possible to the signal-processing interface to avoid signal degradation. In this paper we present the design and implementation of an interface circuit for CMOS sensor systems. A first-order sigma-delta ( Sigma; Delta;) analog-to-digital converter was designed and simulated using Cadence and SpectreS. An experimental prototype of the 10-bit Sigma; Delta; modulator was then fabricated using 1.6 um CMOS technology through MOSIS.